STUDY ON THE MOTOR LEVEL ON 5 TASLIPUP EDARG ht SECONDARY SCHOOL Nr.1 SUCEAVA - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In conclusion, the motor level refers to the stage in which an individual was in terms of movement. We must take into account that the movement skills are formed both in the practice of life and in the specially organized training process. The movement habits of training in daily life (of course I refer mainly to children) appear as a result of long repetition of some movement actions such as: walking, running, jumping, throwing, more precisely the basic motor skills. In the process of training within the school they are modeled, perfected and according to the requirements imposed by the school syllabus, new very varied skills are formed, specific both to the requirements of practicing the different branches of sport (technical procedures) and to performing other actions. of movement, subordinated to the achievement of the objectives of physical education.